Identity juggling and judgments: ESL university students' linguistic identity experiences in their first year of study - Ferraz Neves, Tanya (My University, 2016)
This research project explores the linguistic experiences and the effects of these on the identities of two first-year ESL university students. Using a sociolinguistic framework, it explores the links between language and identity. The data for this study comes from examination essays written based on a first-year Sociolinguistics module in the English I course in the Wits School of Education and interviews conducted with two students. The analysis of this data reveals how these students’ linguistic identities, structured by their different backgrounds, facilitate and constrain the ways in which they adapt to university life. Both students focused on in this research shift in their identities as they attempt to adapt to the increasing number of different fields they encounter at university. Linguistic identity shifts are also evident as they re-enter the old fields in the communities in which they grew up. The two students must work to negotiate these differing identities both within and outside of the university. Bourdieu’s concepts of habitus, capital and field, guide this discussion and help to illustrate how students struggle to negotiate their identity. This study shows that owing to a conflict of capital and the fact that habitus is deeply entrenched layers of linguistic dispositions, linguistic identity is difficult to shift. Despite the fact that the University of the Witwatersrand is a super-diverse environment, with students bringing different kinds of linguistic capital to the various fields within this environment, this research projectargues that students struggle to find a place for themselves within this variety. It shows that the participants seek out affinity groups within which they feel they have sufficient linguistic capital. However, within these groups there is jostling for a linguistic identity as, in the face of policing and linguistic prejudice, they struggle to assert their sense of self in relation to their developing linguistic identities. KEYWORDS: linguistic identity, Discourse, field, habitus, capital, policing, prejudice, investment, voice.
A research report submitted to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Masters in Applied English Language Studies by combination of coursework and research. Johannesburg, 2015
Keywords: Sociolinguistics; Identity (Psychology); Discourse analysis